2014
DOI: 10.1161/str.45.suppl_1.wp331
|View full text |Cite
|
Sign up to set email alerts
|

Abstract W P331: Management of TIA Patients Referred to Ontario Secondary Stroke Prevention Clinics From the Emergency Department

Abstract: Background: Previous studies have found that patients with TIA discharged from the emergency department (ED) have low rates of testing and treatment for secondary stroke prevention. Secondary Stroke Prevention Clinics (SPCs) were established in Ontario to increase access to diagnostics, treatment, and risk factor education programs for patients at risk of stroke. We aimed to characterize the management of patients with transient ischemic attack (TIA) and ischemic stroke referred to the SPCs followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Chart abstractions by trained research members captured demographic and clinical data on all participants from patient charts using previously published and validated methods. 17,18 To reduce sampling bias, all consecutive patients from stroke prevention clinics who completed the DOC screen were asked to complete more detailed neuropsychological assessments, including a cognitive battery and formal mood assessments as outlined in the DOC feasibly study. 12 A complete list of all mood and cognitive assessments completed as part of the DOC study is reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Chart abstractions by trained research members captured demographic and clinical data on all participants from patient charts using previously published and validated methods. 17,18 To reduce sampling bias, all consecutive patients from stroke prevention clinics who completed the DOC screen were asked to complete more detailed neuropsychological assessments, including a cognitive battery and formal mood assessments as outlined in the DOC feasibly study. 12 A complete list of all mood and cognitive assessments completed as part of the DOC study is reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, in our region, the median time from acute hospital admission for stroke to inpatient rehabilitation admission is 9 days. 4 Although the exact time from stroke onset to inpatient stroke rehabilitation ad-mission for our patients was not known, it was felt that this would have had minimal impact on our outcomes given that patients are admitted to rehabilitation so early in their recovery.…”
Section: Authors' Replymentioning
confidence: 99%